GLOSSONIA: CAUSES, SYMPTOMS, TREATMENT (Academicia Globe: Inderscience Research, 2024)
Glossinia is a pathology that is attributed to neurostomatological diseases, for which the appearance of unpleasant sensations in the tongue zone is typical. It has been proven that this disease is poly-etiological in nature with many causes that cause its formation. This disease is most often diagnosed in women over thirty. Women account for about three-quarters of all patients with this disease. This phenomenon is explained by the fact that they have features of the structure of the nervous system. Women are also characterized by the greatest sensitivity to irritants.